Pancreatitis associated with immune checkpoint inhibitors: a pharmacovigilance analysis based on FDA adverse event reporting system (FAERS) database - Huang, Lingli; Wang, Haitian; Wu, Nan (Frontiers in Pharmacology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs)-related pancreatitis is a rare but serious immune-related adverse event (AEs). This study aimed to investigate the risk and profile of ICIs-related pancreatitis on a real world setting by analyzing the FDA Adverse Event Reporting System (FAERS) data.MethodsData were extracted from the FAERS database from the first quarter of 2011 to the third quarter of 2024. Descriptive analysis was used to represent the clinical features, while reporting odds ratio (ROR), proportional reported ratio (PRR), the Bayesian confidence propagation neural network (BCPNN) and the multiple Gamma Poisson Shrinker (MGPS) were used for disproportionation analysis. The time to onset (TTO) was determined by calculating the interval between pancreatitis AEs and drug initiation time.ResultsA total of 1166 cases with positive signals for ICIs-related pancreatitis were screened, involving atezolizumab, durvalumab, avelumab, tislelizumab, pembrolizumab, nivolumab and ipilimumab. There were significant differences in the distribution of gender, weight, age, reporter, reporting country among all ICIs (P < 0.001). As for outcomes, 162 (14.1%) patients died. Avelumab had the highest incidence of death. The results of all four algorithms were consistent, indicating a statistically significant association between overall ICIs and the risk of pancreatitis (ROR 2.44, 95%CI 2.30 - 2.58; PRR 2.43, χ2 979.71; EBGM 2.43, EBGM05 2.29; IC 1.28, IC025 1.22). The ICIs with the highest risk of developing pancreatitis were durvalumab, tislelizumab and avelumab. Avelumab has no significant correlation with pancreatitis in female and patients <65 years old, while other ICIs showed a correlation with pancreatitis, regardless of gender and age. For 491 reports which TTO data were available, the median TTO of ICIs-related pancreatitis was 59.0 days. The TTO of pancreatitis caused by each ICI was statistically significant (P = 0.0029). Ipilimumab had the shortest TTO of 37.5 days, while tislelizumab had the longest TTO of 146.5 days. The stratified analysis by gender and age showed that there was no significant difference in TTO.ConclusionICIs may have a significant association with the occurrence of pancreatitis. In clinical applications, it is necessary to closely monitor the indicators related to pancreatitis in patients, such as abdominal pain, nausea, vomiting, elevated serum amylase or lipase, and take timely intervention measures to reduce the risk of complications.